Molecular Virology, Pathogenesis, and Clinical Management of Human Metapneumovirus: Review Article (Journal of Pharma Insights and Research, 2025)
Human metapneumovirus (hMPV), first isolated in 2001 in the Netherlands, has emerged as a significant respiratory pathogen with global health implications. This paramyxovirus, classified within the Pneumoviridae family, shows remarkable genetic and antigenic diversity through its two major genetic lineages (A and B) and their corresponding subtypes (A1, A2a, A2b, B1, and B2). The virus causes a spectrum of respiratory illnesses, ranging from mild upper respiratory tract infections to severe bronchiolitis, pneumonia, and exacerbation of chronic respiratory conditions. Clinical manifestations often mirror those of respiratory syncytial virus (RSV) infections, presenting diagnostic challenges in clinical settings. The pathogenesis involves direct viral cytopathic effects and immunopathological responses, with the fusion (F) and attachment (G) glycoproteins playing crucial roles in viral entry and host immune response modulation. The virus spreads primarily through respiratory droplets and fomites, with an incubation period of 3-6 days. While hMPV infections occur across all age groups, severe disease manifestations predominantly affect young children (65 years), and immunocompromised individuals. Recent data suggest that hMPV accounts for 5-15% of hospitalizations due to respiratory tract infections in these vulnerable populations. Current diagnostic methods include reverse transcription polymerase chain reaction (RT-PCR), multiplex PCR panels, and rapid antigen detection tests, each offering different advantages in terms of sensitivity, specificity, and turnaround time. Treatment remains primarily supportive, focusing on symptom management and respiratory support when necessary